1994
DOI: 10.1007/bf02917226
|View full text |Cite
|
Sign up to set email alerts
|

Refrigeration of blood samples prior to separation is essential for the accurate determination of plasma or serum zinc concentrations

Abstract: An evaluation of refrigeration (7 degrees C) to prevent falsely high plasma or serum zinc concentrations owing to elapsed time between blood collection and centrifugation was performed. At room temperature (23 degrees C), both plasma and serum zinc concentrations increased significantly, if blood samples were stored uncentrifuged. Plasma zinc concentrations increased 6.3% at 1 h and 40.7% at 24 h, whereas serum zinc concentrations increased only 0.9% at 1 h and 12.5% at 24 h at room temperature. When blood sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…It is also acknowledged that hemolysis could lead to spurious increases in PZC and SZC (6, 1519), although there is little information as to what level of hemolysis creates a concern. Most studies that reported PZC or SZC have limited or no detailed description of how hemolysis was categorized.…”
Section: Introductionmentioning
confidence: 99%
“…It is also acknowledged that hemolysis could lead to spurious increases in PZC and SZC (6, 1519), although there is little information as to what level of hemolysis creates a concern. Most studies that reported PZC or SZC have limited or no detailed description of how hemolysis was categorized.…”
Section: Introductionmentioning
confidence: 99%
“…During this period, they were allowed to drink no more than 250 ml of water, sugar-free carbonated drink, coffee, or tea and they refrained from any food. Blood samples were kept at 4°C, and a portion of the sample was separated for baseline erythrocyte zinc and hematocrit measurements before centrifugation [5]. Plasma and whole blood were stored at )80°C until assayed.…”
Section: Materials and Methods Control Subjects And Loading Testmentioning
confidence: 99%
“…The coefficients of variation of copper and zinc analyses using control samples (unassayed chemistry control serum for zinc and copper, Bio-Rad, Richmond, CA) were less than 4% in our laboratory [5], and the differences in the estimated values of copper and zinc in the standard reference material (#1598: National Institute of Standard and Technology, Gaithersburg, MD) were 8% and 6%, respectively. Plasma ceruloplasmin concentration was measured using a radial immunodiffusion kit (Binding Site, San Diego, CA).…”
Section: Laboratory Analyses and Statisticsmentioning
confidence: 96%
See 1 more Smart Citation
“…15 What all methods of zinc measurement have in common is, that they are prone to influences from preanalytic factors like time elapsed between blood collecting and analysis or zinc contaminations during the process of blood collecting. [16][17][18][19][20][21][22] In this study, we describe the validation of the LT-SYS colometric zinc in vitro diagnostic assay on a Roche cobas c502 analyzer, which is part of a Roche cobas 8000 automated modular platform in the University Clinic Halle (UKH). To date Roche has no zinc assay in its analytic portfolio, rendering it necessary to use third party zinc assays, which are often provided by small to medium scale companies.…”
Section: Introductionmentioning
confidence: 99%